Selective Constraints in Lexical Meaning of the Word - M. V. Vlavatskaya (Научный диалог)
The article is devoted to analysis of the structure of the lexical meaning of the word. The purpose of the article is to substantiate the existence of the selective component in the meaning that limits the collocations, that is, determines the relation of the lexeme with other language units. This component of the meaning unlike others reflects the evolving social practice of the use of the sign and gives it normative, prescriptive nature, and also performs a number of important speech functions - restrictions, regulations or prohibition of the collocations. The author explores the selective constraints on the material of subject-conceptual, expressive and cultural lexis. The study has revealed a large number of examples of selective constraints in meaning of Russian and English words. The analysis allows to argue that selective component of the meaning has important functions in the language - it determines the range of possible compatibility of the word and “supervises” the process of implementing the compatibility of the lexemes. The role of the limiter of collocations in speech is played by three selective components: denotative-selective, connotative-selective and national-cultural - including in its structure and containing various selective semes. Practical value of researches in this area is determined by the fact that knowledge of lexical collocation leads the learners of foreign languages to stupid errors.